The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.ju.0000146719.43269.e8
|View full text |Cite
|
Sign up to set email alerts
|

CURRENT TNM CLASSIFICATION OF RENAL CELL CARCINOMA EVALUATED: REVISING STAGE T3a

Abstract: : We suggest revising the current pT3a classification based on perirenal fat infiltration but rendering a modified pT1/pT2 classification, which resolves pT3a cases without the loss of prognostic validity. Perirenal fat infiltration should not be used to assign T category. Tumors directly infiltrating the adrenal gland should be reclassified as T4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 16 publications
6
49
4
1
Order By: Relevance
“…Patients with adrenal gland involvement have significantly worse survival than those with peri-renal fat involvement (Hank et al, 2003;Siener et al, 2005). Direct ipsilateral adrenal gland involvement in RCC is rare, found only in 2.5% of radical nephrectomy specimens (Hank et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with adrenal gland involvement have significantly worse survival than those with peri-renal fat involvement (Hank et al, 2003;Siener et al, 2005). Direct ipsilateral adrenal gland involvement in RCC is rare, found only in 2.5% of radical nephrectomy specimens (Hank et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…39,40 A study by Huang and colleagues found that a total of 192 out of 662 patients (29%) developed a new onset of GFR lower than 60 mL/min/1.73m 2 and 105 out of 662 patients (16%) developed new onset of GFR lower than 45 mL/min/1.73m 2 following nephrectomy. 41 This study supports the notion that patients who undergo a RN have a significantly higher risk of developing moderately severe CKD and therefore may expe- renal function after partial or radical nephrectomy for rCC rience negative effects on life span and quality of life.…”
Section: What Is Known About Renal Function After Nephrectomy In Humans?mentioning
confidence: 99%
“…Primary adrenal carcinoma that invades the kidney is classified as pT4 disease (Ng & Libertino, 2003;Norton et al, 2005). A number of previous reports have suggested that, analogously, RCC with adrenal gland involvement should be reclassified as 2002-pT4 (Sandock et al, 1997;Han et al, 2003;Siemer et al, 2005;. Based on these investigations, adrenal gland involvement has been classified pT4 in 2009 AJCC TNM staging classification (Edge et al, 2009 …”
Section: Adrenal Gland Involvement In Rccmentioning
confidence: 99%
“…Patients with adrenal gland involvement have significantly worse survival than those with perirenal fat involvement (Han et al, 2003;Siemer et al, 2005). Direct ipsilateral adrenal gland involvement in RCC is rare, found in only 2.5% of radical nephrectomy specimens, and representing 13% of all 2002-pT3a lesions (Han et al, 2003).…”
Section: Adrenal Gland Involvement In Rccmentioning
confidence: 99%
See 1 more Smart Citation